Effects of Inhaled Citronella Oil and Related Compounds on Rat Body Weight and Brown Adipose Tissue Sympathetic Nerve - Irmanida Batubara (Nutrients, 2015)
Citronella oil is one of the most famous Indonesian essential oils, having a distinctive aroma. As with other essential oils, it is crucial to explore the effects of inhalation of this oil. Therefore, the aim of this research was to elucidate the effects of inhalation of citronella oil and its components isolated from Cymbopogon nardus L. (Poaceae), Indonesian local name: “Sereh Wangi” on the body weight, blood lipid profile, and liver function of rats, as well as on the sympathetic nerve activity and temperature of brown adipose tissue. Sprague-Dawley male adult rats fed with high fat diet (HFD) were made to inhale citronella oil, R-(+)-citronellal, and β-citronellol for five weeks, and the observations were compared to those of HFD rats that were not subjected to inhalation treatment. The results showed that inhalation of β-citronellol decreased feed consumption. As a consequence, the percentage of weight gain decreased compared with that in control group and the blood cholesterol level in the β-citronellol group was significantly lowered. Concentration of liver function enzymes were not significantly different among the groups. In conclusion, inhalation of citronella oil, specifically β-citronellol, decreased body weight by decreasing appetite, without any marked changes in liver enzyme concentrations.